2012
DOI: 10.1111/j.1464-5491.2012.03611.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality and Outcomes Framework screening questions for depression in patients with diabetes: effective but non‐efficient

Abstract: Diabet. Med. 29, 957–958 (2012)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Recent systematic reviews have shown depression to be 2–3 times more common in individuals with diabetes than in people who do not have diabetes 4 5. This knowledge spurred the Quality and Outcomes Framework to recommend that people with diabetes are screened for depression by asking two indicatory questions drawn from the Patient Health Questionnaire-2, although this requirement has now been dropped,6 primarily because concern was expressed that this approach resulted in a disproportionately high diagnosis of depression in people with diabetes 7. Fisher and colleagues have shown, in a large sample of people with type 2 diabetes, that 70% of those identified as having depression by the Centre of Epidemiological Studies Depression scale are not clinically depressed, as determined when using the gold standard clinical assessment: the Composite International Diagnostic Interview score 8.…”
Section: Introductionmentioning
confidence: 99%
“…Recent systematic reviews have shown depression to be 2–3 times more common in individuals with diabetes than in people who do not have diabetes 4 5. This knowledge spurred the Quality and Outcomes Framework to recommend that people with diabetes are screened for depression by asking two indicatory questions drawn from the Patient Health Questionnaire-2, although this requirement has now been dropped,6 primarily because concern was expressed that this approach resulted in a disproportionately high diagnosis of depression in people with diabetes 7. Fisher and colleagues have shown, in a large sample of people with type 2 diabetes, that 70% of those identified as having depression by the Centre of Epidemiological Studies Depression scale are not clinically depressed, as determined when using the gold standard clinical assessment: the Composite International Diagnostic Interview score 8.…”
Section: Introductionmentioning
confidence: 99%